Stelis concava (Orchidaceae, Pleurothallidinae), a new species from the Brazilian Atlantic Forest - Miranda, Marcelo Rodrigues; Furtado, Samyra Gomes; Menini Neto, Luiz (Phytotaxa, 2015)
A new species of Stelis from Brazil is described and illustrated. Stelis concava is the third species of the S. sect. Humboldtia known in Brazil and the first described in the Atlantic Forest.